Ag/Au Alloy LSPR Engineering by Co‐deposition of RF‐Sputtering and RF‐PECVD - Gholamali, Hediyeh; Shafiekhani, Azizollah; Darabi, Elham; Elahi, Seyed Mohammad (Applied organometallic chemistry, 2018)
Silver‐Gold alloy/diamond like carbon (Ag‐Au/DLC) nanocomposite films were prepared by co‐deposition of RF‐sputtering and RF‐PECVD on glass substrates by using acetylene gas and silver‐gold target. The deposition process was carried out at room temperature in one minute with the variable parameters of initial pressures and RF powers. X‐ray diffraction analysis demonstrated the formation of Ag/Au alloy nanoparticles with a face‐centered cubic (FCC) structure. Localized surface plasmon and optical properties of Ag‐Au alloy nanoparticles were studied by UV‐visible spectrophotometry which showed that increasing RF power and initial pressure cause a redshift in all samples. Moreover, the effect of RF power and initial pressure on the size and shape of nanoparticles were studied by 2D Atomic force microscopy images. Energy dispersive X‐ray spectroscopy revealed the formation of Ag‐Au/DLC nanoparticles and the percentages of C, Ag, Au and O in all samples. The applied method for Ag/Au alloy preparation is the one step and low‐cost method which makes the samples ready for sensing application. Ag/Au alloy nanoparticles embedded in carbon film by co‐deposition of RF‐sputtering and RF‐PECVD methods were fabricated. The sizes of nanoparticles can be controlled by proper pressure and RF power.